Exploring the connections between giraffe skin disease and lion predation - Muneza, A; Linden, D; Kimaro, M; Dickman, A; Macdonald, D; Roloff, G; Hayward, M; Montgomery, RM (Wiley, 2021)
Rates at which predators encounter, hunt, and kill prey are influenced by, among other things, the intrinsic condition of prey. Diseases can considerably compromise body condition, potentially weakening ability of afflicted prey to avoid predation. Understanding predator-prey dynamics is particularly important when both species are threatened, as is the case with lions (Panthera leo) and giraffes (Giraffa camelopardalis). Importantly, an emergent disease called giraffe skin disease (GSD) may affect predatory interactions of lions and giraffes. Hypotheses suggest GSD may negatively affect the likelihood of giraffes surviving lion attacks. We evaluated giraffe-lion interactions in Ruaha National Park, Tanzania, where 85% of the giraffe population has GSD. We monitored lion hunting behavior and estimated proportion of the giraffe population with GSD and evidence of ‘lion marks’ from assumed previous lion predation attempts (i.e. claw marks, bite marks, and missing tails). Although we recorded lions hunting and feeding on 16 different prey species, giraffes represented the largest prey category (27%; n = 171 of 641). For age and sex cohorts combined, 26% (n = 140 of 548) of encountered giraffes displayed evidence of previous lion predation attempts. Occurrence of lion marks was higher for adults and males in the giraffe population, suggesting that these individuals were more likely to survive lion attacks. We also found marginal evidence of a positive relationship between giraffes with severe GSD and occurrence of lion marks. Our results identify giraffes as important prey species for lions in Ruaha National Park and suggest that GSD severity plays a minor role in likelihood of surviving a lion attack. This is the first study to explore connections between lion predation and GSD. We explore the ecological implications of disease ecology on predator-prey interactions and consider opportunities for future research on causal links between GSD and giraffe vulnerability to lion predation.